The Association between Obesity and Cognitive Function in Otherwise Healthy Premenopausal Arab Women - Abdulaziz Farooq; Ann-Marie Gibson; John J. Reilly; Nadia Gaoua (Journal of Obesity)
Objective. To examine the association between obesity and cognitive function in healthy premenopausal women. Methods. From a cohort of 220 women, 98 were randomly selected that provided complete data. Body composition was examined by dual-energy X-ray scan. All participants completed the Cambridge Neuropsychological Test Automated Battery (CANTAB) to assess cognitive performance in three domains: attention, memory, and planning executive function. The Reaction Time (RTI) test was used to assess motor and mental response speeds; the Stockings of Cambridge (SOC) test was used to assess planning executive function. For memory assessment, the Delayed Match to Sample (DMS), Pattern Recognition Memory (PRM), and Spatial Span (SSP) tests were used to assess forced choice recognition memory, visual pattern recognition memory, and working memory capacity, respectively. Results. 36 (36.7%) were morbidly obese, 22 (22.4%) obese, and 23 (23.5%) overweight. Performance on RTI and SOC planning ability were not associated with body mass index (BMI). DMS mean time to correct response, when stimulus is visible or immediately hidden (0 ms delay), was higher by 785 ± 302 ms (milliseconds) (p=0.011) and 587 ± 259 ms (p=0.026) in morbidly obese women compared to normal weight women. Memory span length was significantly lower in overweight (5.5 ± 1.3, p=0.008) and obese women (5.6 ± 1.6, p=0.007) compared to normal weight (6.7 ± 0.9). DEXA-assessed body fat (%) showed similar associations as BMI, and latency to correct response on DMS and PRM was positively correlated with percentage of body fat, but not with VO2 max. Conclusion. In otherwise healthy premenopausal women, obesity did not impact accuracy on cognitive tasks related to attention, memory, or planning executive function, but morbid obesity was associated with higher latency to correct response on memory-specific tasks and lower memory span length.